Emergence of Potential-Controlled Cu-Nanocuboids and Graphene-Covered Cu-Nanocuboids under Operando CO2 Electroreduction - Thanh Hai Phan; Karla Banjac; Fernando P. Cometto; Federico Dattila; Rodrigo García-Muelas; Stefan J. Raaijman; Chunmiao Ye; Marc T. M. Koper; Núria López; Magalí Lingenfelder (My University, 2021)
Emergence of Potential-Controlled Cu-Nanocuboids and Graphene-Covered Cu-Nanocuboids under Operando CO2 Electroreduction
Keywords: Cu-Nanocuboids; Điện khử CO2 (CO2RR); Operando